Factors Influencing Value Creation on Brand Trust in Hotel Business: Case Study of 3-, 4- And 5-Star Hotels in Indonesia During the Covid-19 Pandemic - Riyadi, Agus; Kristanti, Eunike Yoanita (UUM Press, 2021)
This research investigates the society or guests’ perception of the value creation and brand trust and aims to examine the effect of value creation on brand trust in 3-, 4-, and 5-star hotels in Indonesia during the COVID-19 pandemic. This research adopted the quantitative method and used probability sampling to determine the sample size. The data were collected using questionnaires via Google Forms and also distributed to respondents who had stayed in 3-, 4-, and 5 star hotels in Indonesia during the COVID-19 pandemic with a total respondents of 99 people. Hypotheses were tested and the findings suggest that value creation has a significant impact on brand trust. The results suggested that hotel brands in Indonesia need to create values that are appreciated by the society as a whole and hotel guests. However, hotel brands in Indonesia still need to improve their creations of value to further boost brand trust for hotel brands in Indonesia in order to improve the hotel performance. The development of a business-oriented analytical framework that aids practitioners in assessing and approaching the opportunities posed by value creation on brand trust is further discussed in the study. The paper introduces an analytical and fresh perspective on value creation and brand trust particularly in a hotel industrial marketing context.